2021
DOI: 10.1097/pcc.0000000000002786
|View full text |Cite
|
Sign up to set email alerts
|

Super-Refractory Status Epilepticus in Children: A Retrospective Cohort Study

Abstract: To characterize the pediatric super-refractory status epilepticus population by describing treatment variability in super-refractory status epilepticus patients and comparing relevant clinical characteristics, including outcomes, between super-refractory status epilepticus, and nonsuper-refractory status epilepticus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
(105 reference statements)
1
14
0
Order By: Relevance
“…These findings are concordant with data supporting that super-refractory status epilepticus causes worse neurological outcomes and lower rates of return to baseline cognitive function than non-super-refractory status epilepticus ( 18 ). One study reported that 58% of patients with NORSE had neurocognitive deficits, of which 30% were severe ( 19 ).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are concordant with data supporting that super-refractory status epilepticus causes worse neurological outcomes and lower rates of return to baseline cognitive function than non-super-refractory status epilepticus ( 18 ). One study reported that 58% of patients with NORSE had neurocognitive deficits, of which 30% were severe ( 19 ).…”
Section: Discussionsupporting
confidence: 89%
“…Two infusions with different drugs were utilized in 32.3% and three or more different drugs were used in 19.4% of cases. Most of the patients with SR SE (96.8%) received midazolam as the first choice [54]. The same study observed that SRSE patients had delayed initiation of first non-ben-zodiazepine antiseizure medication in comparison with the non-SRSE patients (149 min vs. 62 min; p = 0.030).…”
Section: Super-refractory Status Epilepticusmentioning
confidence: 76%
“…Vasquez et al showed that pediatric SRSE patients with delayed non‐BZD ASM initiation had more medical complications, higher mortality, and lower return to neurological baseline than non‐SRSE patients. However, these associations were not adjusted for potential confounders 17 . Delayed BZD use and underdosing were associated with SE refractoriness and unfavorable outcomes 18 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, data from adults might not directly apply to children since the physical and neurochemical characteristics of the developed brain differ from those of the developing brain. However, several recent studies on children and adolescents with SE, refractory SE (RSE), and super‐refractory SE (SRSE) have been published 9‐18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation